STANDING STOK IKAN PAWEH (Osteochillus hasselti) dan KONDISI LINGKUNGAN DANAU LUBUK SIAM DESA LUBUK SIAMKECAMATAN SIAK HULU PROVINSI RIAU - Iswara, Anggi Widya; Fauzi, Muhammad; Fajri, Nur El (Asian Journal of Aquatic Sciences, 2019)
Osteochillus hasselti was commonly inhabit the Lubuk Siam Lake. A research aims to understand the standing stock of O. hasselti in that lake was conducted in July to August 2018. The fish was sampled everyday for 10 days in July and 10 days in August, in 3 sampling points (in the inlet area, in the middle of the lake, and the outlet) using gill nets. The standing stock was analyzed using Leslie method. Results shown that the initial population (No) of the fish was 315 kg and the final population (Nt) was 301 kg and the exploitation level was 8%. The water quality parameter shown that temperature was 27-28oc, clarity 63-95 cm, pH = 6 and dissolved oxygen was 5.32–5.40 mg/L. Data obtained indicate the water quality in the Lubuk Siam Lake is good and it is able to support the life of O. hasselti